Pattern of Burn Injury in Children Presented to Dhaka Shishu (Children) Hospital - Alam, Muhammad Rashedul; Ullah, Md Saif; Biswas, Prosanto Kumar (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Children are mostly affected in burn injury at our country like other low and middle income countries (LMICs). Approximately 90% of the burns occur in under developed countries, which generally lack the necessary infrastructure to reduce the incidence and severity of burns. Objectives: This study was done to investigate the pattern of burn cases admitted to Dhaka Shishu (Children) Hospital (DSH). Methods: This was a retrospective study conducted over the period of one year from January 2019 to December 2019 at Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh. The data was collected from the patients record section of the hospital. Patients characteristics (e.g. age, sex), causes and severity of injury, outcome, hospital stay and seasonal variation were analized in this study. Results: A total of 91 patients were admitted during study period of one year. This study consisted of 53 male patients (58.24%) and 38 female patients (41.76%) with male to female ratio of 1.3:1. The most frequently hospitalized burn patients were in the age group 3-5 years, which accounted for 30.77% of patients. Burns were more common during winter season followed by autumn season, with 43 cases (47.25%) and 18 cases (19.78%) respectively. The highest number of admissions was during the month of December. Scald burn was the most common cause of burn injury in our study which accounted for 83 cases out of 91 cases (91.2%). Flame burn occured in 3(3.29%) patients. There were 2 cases of electric burn and 2 cases of contact burn during this study period. One patient was with chemical burn. Scald burn was the most common cause of burn injury in this study which accounted for 83 cases out of 91 cases (91.2%). Flame burn occured in 3(3.29%) patients. There were 2 cases of electric burn and 2 cases of contact burn during this study period. One patient was with chemical burn. Conclusion: The most frequently hospitalized burn patients were in the age group 3-5 years and more common during winter season. Most of the burn occured in children are scald in our country due to accidental fall of worm liquid. Superficial epidermal and dermal burns are treated conservatively, but deep burns may require surgical treatment. DS (Child) H J 2020; 36(2): 134-137